PENGARUH SOCIAL MEDIA MARKETING YOUTUBE, INSTAGRAM, DAN TWITTER TERHADAP BRAND AWARENESS PADA GENERASI Z (Studi Kasus Pada Radio Play99ers 100FM Bandung) - Febrianti, Agatha Indah; Saputri, Marheni Eka (JURISMA : Jurnal Riset Bisnis & Manajemen, 2022)
Internet users has increased very rapidly in Indonesia. One of them is generation Z. This generation attached to the social media and the company also have using social media is one of the media to raise brand awareness, it’s also used by Radio Play99ers 100FM Bandung. Social media used by Radio Play99ers consisting of three platform there are youtube, instagram, twitter. The purpose of this research is to find out if social media marketing youtube, instagram, and twitter depend on the brand awareness. A method of data collection in this research using a questionnaire to be distributed to 100 respondents. The method of analysis of the data used to research is the method descriptive analysis and simple linear regression analysis. Processing data was done by using IBM software SPSS 25 for windows. In simultaneous in terms of t test, there is the influence social media marketing youtube, instagram, twitter against brand awareness in generation Z (case studies on the Radio Play99ers 100FM Bandung). The influence of social media marketing affects brand awareness of 0,330 or equal to 33% and the other 0,670 or 67% influenced by other variables that not include in this research. Keywords: Brand Awareness, Generasi Z, Social Media Marketing